Térképek a nemzeti terjeszkedés szolgálatában - Marjanucz, László (Közép-Európai Közlemények, 2009)
Before and during the First World War the nationalities of the Austrian-Hungarian Monarchy and the Antant supporting them have elaborated and published several maps serving as means of propaganda. These maps show which territories the nationalities wanted to obtain from the Monarchy, and some of them even exhibited the way the Monarchy wanted to be split. The paper presents and analyzes the Check-Slovak, Roumanian and South-slavic maps, and also those English and French ones that were published in the Antant countries.